Nanotechnology and the Environment - Sen, Mousumi (IntechOpen, 2020)
Nanotechnology is a vibrant area of research and a growing industry. The core scientific principles and applications of this interdisciplinary field bring together chemists, physicists, materials scientists, and engineers to meet the potential future challenges for sustainable development through new technologies and preparation of advanced materials with sustainable environmental protection. This book on Nanotechnology and the Environment includes the design and the sophisticated fabrication of nanomaterials along with their potential energy and environmental applications. This book is a significant contribution towards the development of the knowledge for all advanced undergraduate, graduate level students, researchers, and professional engineers leading in the fields of nanotechnology, nanochemistry, macromolecular science and those who have interest in energy and environmental science.